The Relationship of Educational Level With Knowledge About the Fitness of Drinking Water Sources in Gempol Village, Karanganom Subdistrict, Klaten District - Arvita Ningtyas; Rezania Asyifiradayati (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Water is a necessity of life, such as washing clothes, washing vehicles, bathing, defecating, cooking, drinking, purifying, ablutions, watering yard plants, providing water for livestock and pets, and other needs. Poor water quality has an impact on health and can even be life-threatening. This study aims to determine the relationship between education about the suitability of drinking water sources and the level of knowledge in Gempol Village, Karanganom District, Klaten Regency. This study is a quantitative study with a research design and a cross-sectional approach. The research was conducted in Gempol Village, Karanganom District, Klaten Regency, from October to November 2023. The study population included residents of Gempol Village, consisting of 18 neighbourhood associations with 800 family cards. A total of 116 respondents, who were selected through proportional sampling calculations, were involved in this study. Data were collected through questionnaires and observation sheets. Bivariate data analysis with Fisher exact test processed using SPSS version 26. The results showed a relationship between education level and knowledge about the feasibility of drinking water sources (p-value = <0.0001) <0.05. It is recommended that the Gempol village government implement an ongoing educational program to increase community awareness about the importance of clean water and how to ensure the suitability of drinking water sources. This program can include counselling, workshops, seminars, and public campaign. Itit is suggestethat health workerss provide accurate advice and information to the community on how to choose safe drinking water sourcestoo increase community knowledge about the quality of drinking water sources that meet health requirements. Keywords: Drinking Water, Education, Suitability of Drinking Water Source, Knowledge